GAMBARAN HISTOLOGIK GASTER PADA HEWAN COBA SELAMA 24 JAM POSTMORTEM - Lilingan, Megi; Kalangi, Sonny J.R.; Wangko, Sunny (Universitas Sam Ratulangi, 2016)
Abstract: Studies about postmortem histological changes in stomach is still very limited. This study aimed to obtain histological changes of stomach in several time intervals during 24 hours postmortem. This is a descriptive study using pig as model. Samples of fundus tissue taken in several time intervals in postmortem were as follows: 0 hour, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, and 24 hours. The results showed that the earliest histological change was identified at 2 hours postmortem as fundic gland cell congestion. At 7 hours postmortem the contours of some fundic glands and borders of their cells were not distinct anymore, meanwhile their nuclei were dispersed among the remnants of fundic glands. At 18-24 hours postmortem, almost all fundic glands could not be indetified. Conclusion: The earliest histological change of stomach was identified at 2 hours postmortem as fundic gland cell congestion, followed by necrosis of fundic gland cells since 7 hours postmortem.Keywords: postmortem histological changes, fundic glands, postmortem interval Abstrak: Studi mengenai perubahan gambaran histologik gaster postmortem masih sangat terbatas. Penelitian ini bertujuan untuk mendapatkan gambaran histologik gaster berdasarkan variasi waktu selama 24 jam postmortem. Jenis penelitian ini deskriptif dengan menggunakan babi sebagai hewan coba. Sampel jaringan fundus diambil pada interval waktu 0 jam; 1 jam; 2 jam; 3 jam; 4 jam; 5 jam; 6 jam; 7 jam; 8 jam; 9 jam; 12 jam; 14 jam; 16 jam; 18 jam; 20 jam; 22 jam; 24 jam postmortem. Hasil penelitian memperlihatkan bahwa perubahan histologik gaster babi mulai teridentifikasi pada 2 jam postmortem sebagai kongesti kelenjar fundus. Pada 7 jam postmortem bentuk dari beberapa kelenjar fundus dan batas-batas sel tidak jelas, sementara itu inti sel mulai terpisah di antara sisa-sisa kelenjar fundus. Pada 18-24 jam postmortem, umumnya kelenjar fundus sudah tidak bisa diindentifikasi. Simpulan: Perubahan histologik awal dari gaster dapat diidentifikasi pada 2 jam postmortem dengan gambaran kongesti kelenjar fundus, diikuti oleh nekrosis kelenjar fundus sejak 7 jam postmortem. Kata kunci: perubahan histologik postmortem, kelenjar fundus, waktu postmortem.